Avaliação da atividade de enzimas que hidrolisam nucleotídeos e nucleosídeo de adenina em pacientes com melanoma cutâneo. - Manica, Aline (2015)
The Cutaneous Melanoma (CM) is considered responsible for most deaths related to skin cancer. The frequency of new cases and incidence is increasing, especially among young people. In Brazil the highest rates are in the South because individual tissue composition and the population habits: the majority of Caucasians exposed to intermittent solar radiation without sun protection. Risk factors for the development of CM can be both genetic, and environmental, but recent surveys show that factors not yet studied might be favoring an increase in the number of cases of MC in recent decades. Moreover cancer cells change and activate various physiological mechanisms, among them platelets, which besides the function tromboregulation are also involved in tumor progression. In the platelet surface we meet various enzymes, among them enzymes that are part of the purinergic system. Thus, this study evaluated the hydrolysis of nucleoside and nucleotides adenine in MC patients and controls, in order to elucidate how the system is acting purinergic this cancer. Furthermore we selected 23 patients with post-treatment CM and 25 control patients. The average age for the CM group was 48 ± 12.5 years and for the control group was 47 ± 13 years. The percentage of affected women was higher than men: 65%. The majority of the MC group had surgical removal of the tumor among 2013-2014 and the most affected body parts were the lower and upper limbs, trunk and head. Were analyzed the activity of enzymes that hydrolyze nucleotides ATP, ADP and AMP and the nucleoside adenosine through enzymatic enzymes activity E-NTPDase, E-5'-Nucleotidade, Adenosine Deaminase (ADA) in platelets, alkaline phosphatase (ALP) and ADA in serum and the E-NTPDase and E-5'-Nucleotidase expression. The results demonstrated a decrease in hydrolysis of the nucleotides ATP, ADP and AMP in platelet, and an increased adenosine hydrolysis by the ADA in both serum and platelets. The ALP activity was also increased in patients with CM when compared with control patients. For the expression E-NTPDase and E-5'-nucleotidase there was no significant difference between groups. Thus, in our study, was found a decrease extracellular ATP degradation rate, increased ADA activity in platelets and serum, being beneficial for patients with CM. So, concluded this way a protective activity against multiple primary neoplasms, by increasing extracellular ATP in patients who had surgical removal CM. The purinergic signaling would prevent the growth of a new tumor because ATP is not being degraded by promoting the platelet signaling to activate the lymphocyte immune response.